Improved local and regional control with radiotherapy for Merkel cell carcinoma of the head and neck. Issue 1 (14th June 2016) - Strom, Tobin; Naghavi, Arash O.; Messina, Jane L.; Kim, Sungjune; Torres–Roca, Javier F.; Russell, Jeffery; Sondak, Vernon K.; Padhya, Tapan A.; Trotti, Andy M.; Caudell, Jimmy J.; Harrison, Louis B.
Abstract: Background: We hypothesized that radiotherapy (RT) would improve both local and regional control with Merkel cell carcinoma of the head and neck. Methods: A single‐institution institutional review board‐approved study was performed including 113 patients with nonmetastatic Merkel cell carcinoma of the head and neck. Postoperative RT was delivered to the primary tumor bed (71.7% cases) ± draining lymphatics (33.3% RT cases). Results: Postoperative local RT was associated with improved local control (3‐year actuarial local control 89.4% vs 68.1%; p = .005; Cox hazard ratio [HR] 0.18; 95% confidence interval [CI] = 0.06–0.55; p = .002). Similarly, regional RT was associated with improved regional control (3‐year actuarial regional control 95.0% vs 66.7%; p = .008; Cox HR = 0.09; 95% CI = 0.01–0.69; p = .02). Regional RT played an important role for both clinical node‐negative patients (3‐year regional control 100% vs 44.7%; p = .03) and clinical/pathological node‐positive patients (3‐year regional control 90.9% vs 55.6%; p = .047). Conclusion: Local RT was beneficial for all patients with Merkel cell carcinoma of the head and neck, whereas regional RT was beneficial for clinical node‐negative and clinical/pathological node‐positive patients. © 2016 Wiley Periodicals, Inc. Head Neck 39: 48–55, 2017